Depression status in relation to caries experience and salivary physiochemical characteristics among 15 years old students in Al-Swera city - Wassit Governorate-Iraq - Huda S Khiala; Ban S Diab (College of Dentistry/ University of Baghdad, 2015)
Background: Depression is a common mental disorder that presents with depressed mood;it can become chronic or recurrent and affect dental health .Thus this research aimed to assess the prevalence and severity of dental caries among students with different grade of depression in relation to physicochemical characteristics of stimulated whole saliva. Materials and methods: The total sample involved for depression status assessment is composed of 800 students for both gender aged 15 years old that were selected randomly , This was performed using children depression inventory (CDI) index that divided the students into four groups of depression(low or average grade, high average grade, elevated grade and very elevated grade). The diagnosis and recording of dental caries was by using decay, Missing, Filled surface index (DMFs); and according to the criteria ofManji et al (1989), Salivary samples was collected from 30 student with very elevated grade of depression and 30 from low or average grade under standardized conditions, then analyzed for measuring salivary flow rate and viscosity, in addition to estimation salivary elements that includes total protein, zinc, copper, chromium and Lithium. Results: the data of the present study showed that the percentage of Caries free students was higher among very elevated grade (8.60%) followed by low or average grade (8.52%), the less was among elevated grade of depression (5.04%).Concerning caries experience, the highest result was among elevated grade of depression followed by low or average grade, the lower result was among high average grade. While the sever grade of dental caries (D4) was found to be highly significant differ among different grade of depression, The data analysis of salivary elements found that the protein was higher in very elevated grade than low or average grade while other elements show the opposite result with significant concerning copper and zinc among very elevated grade that show significant difference. DMFs correlated negatively with salivary flow rate among low or average grade and very elevated grade; while concerning salivary viscosity, the correlation was direct with DMFs. With highly significant in very elevated grade, Salivary elements show positive relation with not significant except copper that show negative relation with significant. Conclusion: The results of the current research revealed that depression status had an adverse effect on salivary physicochemical characteristics and dental status including caries experience